2017
DOI: 10.1111/1440-1681.12805
|View full text |Cite
|
Sign up to set email alerts
|

Lower muscle tissue is associated with higher pulse wave velocity: A systematic review and meta‐analysis of observational study data

Abstract: Muscle loss and arterial stiffness share common risk factors and are commonly seen in the elderly. We aimed to synthesise the existing literature on studies that have examined this association. We searched electronic databases for studies reporting correlations or associations between a measure of muscle tissue and a measure of arterial stiffness. Meta-analysis was conducted using Fisher's Z-transformed r-correlation (r ) values. Pooled weighted r and 95% confidence intervals were calculated in an inverse-vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Although the focus of this systematic review has been on relatively healthy subjects, the association between skeletal muscle health and vascular dysfunction has been demonstrated in other populations. A recent meta-analysis examined macrovascular function through pulse wave velocity and demonstrated that lower muscle tissue is associated with higher arterial stiffness in populations with diabetes and kidney disease [21]. This association has been demonstrated in healthy children as well, in which researchers determined that arterial stiffness (measured by CIMT) is negatively associated with muscular strength [79].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the focus of this systematic review has been on relatively healthy subjects, the association between skeletal muscle health and vascular dysfunction has been demonstrated in other populations. A recent meta-analysis examined macrovascular function through pulse wave velocity and demonstrated that lower muscle tissue is associated with higher arterial stiffness in populations with diabetes and kidney disease [21]. This association has been demonstrated in healthy children as well, in which researchers determined that arterial stiffness (measured by CIMT) is negatively associated with muscular strength [79].…”
Section: Discussionmentioning
confidence: 99%
“…Given that many of the risk factors for sarcopenia and cardiovascular disease are shared, it is not surprising that there is an association between measures of vascular dysfunction and muscle health. Existing reviews solely target arterial stiffness as an indicator of vascular dysfunction and its' association with skeletal muscle health [21]. This systematic review takes a broader approach and examines other validated indices of vascular function including microvascular function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations